2008
DOI: 10.1182/blood-2008-03-147033
|View full text |Cite
|
Sign up to set email alerts
|

SCF-mediated mast cell infiltration and activation exacerbate the inflammation and immunosuppression in tumor microenvironment

Abstract: Despite the evidence for the role of inflammation in cancer initiation, promotion, and progression, the precise mechanism by which the inflammation within tumor is orchestrated by inflammatory cells remains to be determined. Here IntroductionChronic inflammation, a "promoting force" in the tumor microenvironment, has long been known to be commonly braided with the initiation, promotion, and progression of tumorigenesis. [1][2][3][4][5] To date, however, it is still incompletely understood how the inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
273
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(291 citation statements)
references
References 53 publications
10
273
2
6
Order By: Relevance
“…SCF is a well-known chemoattractant for MC migration in the context of cancer. 18 Therefore, we added various concentrations of SCF blocking antibody in the migration assay. Inhibition of SCF resulted in up to 65% reduction of MC recruitment to Caco2, but had no effect on that of HT29 (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCF is a well-known chemoattractant for MC migration in the context of cancer. 18 Therefore, we added various concentrations of SCF blocking antibody in the migration assay. Inhibition of SCF resulted in up to 65% reduction of MC recruitment to Caco2, but had no effect on that of HT29 (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…38 The importance of SCF in attracting MC into tumor environment was previously demonstrated by the migration of mouse primary MC toward mouse H22 hepatocarcinoma cells. 18 Surprisingly, HT29 colon cancer cells induced MC chemotaxis partly via the secretion of CCL15, while no SCF-induced migration was involved. This may reflect the intrinsic biological difference among individual colon cancers.…”
Section: Discussionmentioning
confidence: 97%
“…Using a transplanted hepatocarcinoma model, Huang and colleagues (12) have recently demonstrated that mast cells can accumulate in the TME and exacerbate inflammation and immunosuppression via the SCF/c-kit signaling pathway. Moreover, they discuss a close loop between mast cells, MDSCs, and regulatory T cells (Treg) in creating a potent suppressive TME.…”
Section: Introductionmentioning
confidence: 99%
“…Once mast cells are attracted to tumors by chemo-attractants, such as stem cell factor (SCF), they are triggered to secrete molecules that act as growth factors, stimulating tumor growth, angiogenesis, and metastasis. Mast cells thus promote the tumor microenvironment remodeling and tumor growth, increasing the secretion of inflammatory chemicals and the activity of NF-kappaB, which augments the suppression of Tcells and natural killer cells in tumors (Huang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%